Indigenous practitioners' views on causes of female infertility - Banabotlhe G. Baakeleng; Abel J. Pienaar; Puledi M. Sithole; Simangaliso L. Mashego (AOSIS, 2023)
Background: The use of indigenous practices has increased remarkably throughout the world. Subsequently, society uses this practice for the treatment of various health problems, including infertility. This research focussed on the role of indigenous practitioners (IPs) using a holistic approach to explore the causes of infertility in women. Aim: This study aimed to explore and describe the views of IPs on the causes of female infertility in Ngaka Modiri Molema health district. Setting: The study was conducted in Ngaka Modiri Molema, North West Province, one of the most rural provinces in South Africa. Methods: The study followed a qualitative explorative design. A purposive sampling technique identified five IPs who were experts in managing infertility. Individual semi-structured interviews were conducted, and data analysis used Creswell's method of qualitative data analysis. Results: Findings revealed that IPs offered a wide range of services in the treatment and management of infertility among rural women. Hence, the following themes emerged, namely, history taking regarding infertility, treatment of infertility and holistic care on infertility. Conclusion: The IPs are important providers of healthcare in the management of infertility in indigenous communities. The findings revealed that there are various causes of female infertility according to the indigenous healthcare system. Contribution: In contribution, the study described the unique practices found in the community as executed by the IPs. This care focusses on holistic care, including treatment and continuous care for the healthcare user and the family. Noteworthy to mention, this holistic care extends to subsequent pregnancies. However, there is a need for further research to valorise the indigenous knowledge unearthed in this study.